The role of Olfr78 in the breathing circuit of mice - Torres-Torrelo, Hortensia; Ortega-Sáenz, Patricia; Macías, David; Omura, Masayo; Zhou, Ting; Matsunami, Hiroaki; Johnson, Randall S.; Mombaerts, Peter; López-Barneo, José (Nature (London), 2018)
In response to hypoxia, neuron-like oxygen-sensitive glomus cells in the carotid body release neurotransmitters that rapidly activate afferent sensory fibres that stimulate the respiratory centre and induce hyperventilation1, although the mechanisms by which glomus cells detect changes in blood oxygen tension remain unclear2,3. [...]in 2017 a new cryorecovery was ordered and the resulting heterozygous mice were shipped directly to Seville and Duke Universities, without passing through the Frankfurt animal facility. [...]single dissociated glomus cells of wild-type and Olfr78-/- FRA mice, loaded with Fura-23,14, showed no difference in their increases of cytosolic Ca2+ levels to hypoxia (Fig. 2e-g). [...]our results at the cellular level are consistent with our results at the whole-animal level. Hortensia Torres-Torrelo1,2, Patricia Ortega-Sáenz1,2, David Macias3, Masayo Omura4, Ting Zhou5, Hiroaki Matsunami5,6, Randall S. Johnson3,7, Peter Mombaerts4 & José López-Barneo1,2· Instituto de Biomedicina de Sevilla (IBiS), Hospital Universitario Virgen del Rocío/CSIC/Universidad de Sevilla, Seville, Spain. 2Centro de Investigación Biomédica en Red sobre Enfermedades Neurodegenerativas (CIBERNED), Seville, Spain. 3Department of Physiology, Development & Neuroscience, University of Cambridge, Physiological Laboratory, Cambridge, UK. 4Max Planck Research Unit for Neurogenetics, Frankfurt, Germany. department of Molecular Genetics and Microbiology, Duke University Medical Center, Durham, NC, USA. department of Neurobiology and Duke Institute for Brain Sciences, Duke University Medical Center, Durham, NC, USA. department of Cell and Molecular Biology, Karolínska Institute, Stockholm, Sweden. ·e-mail: lbarneo@us.es Received: 13 February 2017; Accepted: 7 June 2018; Published online: 26 September 2018 Author contributions All authors participated in the design of the experiments.